(untitled) (Medical Forum Monthly, 2021)
Objective: To assess the knowledge, attitude and practices regarding malaria in rural and urban suburbs of Peshawar and Mardan districts, Khyber Pakhtunkhwa, Pakistan. Study Design: Descriptive study Place and Duration of Study: This study was conducted at the two major tertiary care hospitals of hospitals of Khyber Pakhtunkhwa from September 2020 to February 2021. Materials and Methods: A structured questionnaire was used which contained detailed information about the demography, knowledge, attitude and practice of the enrolled inhabitants. Results: Most study subjects (80% rural, 90% urban) knew facts about malaria. 59% rural, 92% urban knew that mosquitoes were the vectors. 31.5% rural and 43% urban community knew about destruction of mosquito sites. 84% urban while 46.5% rural inhabitants were aware of anti-mosquito sprays. 55% of the rural population and 38% of urban society was not practicing any measures against malarial prevention. Conclusion: Our community is familiar with the symptoms of malaria and its mode of transmission. The knowledge about preventive measures and vector control was deficient in rural areas. The overall situation needs to be strengthened.